Pengaruh Brand Awareness dan Brand Characteristic terhadap Keputusan Pembelian Produk Wardah pada Fakultas Ekonomi dan Bisnis Universitas Nusa Nipa - Suci Imaniar; Antonius Phillipus K.Gheta; Dimas Realino (Universitas Nusa Nipa Maumere, 2025)
This study aimed to (1) Describe Brand Awareness, Brand Characteristic and Purchasing Decisions Of Wardah products, (2) Analyze the influence of Brand Awareness on Wardah product purchasing decisions, (3) Analyze the combined influence of Brand Awareness and Brand Characteristic on Wardah product purchasing decisions. The research design used was associative with a quantitative approach. The sample size was determined using Cochran’s formula, totaling 100 respondents, all of whom were female students using Wardah products at the Faculty of Economics and Business. Data were collected through questionnaires and analyzed using inferential statistics, specifically multiple linear regression. Hypotheses were tested using the T-tested and F-test. The results of the study indicated that (1) Brand Awareness (X1) had a significant partial influence on purchasing decisions (Y) with T-value of 2.853 >1.97, (2) Brand Characteristics (X2) had a significant partial influence on purchasing decisions (Y), with a T-value of 3.731 > 1,97, and (3) Simultaneously, Brand Awareness (X1) and Brand Characteristics (X2) significantly influenced purchasing decisions (Y), with an F-value of 62.315 > 3.07.